Kompetisi Diplomasi: Taiwan (ROC) versus Tiongkok (PRC) di Kepulauan Solomon tahun 2016-2019 - Santoso, Victoria Amandani; Windiani, Reni; Paramasatya, Satwika (Jurnal Hubungan Internasional, 2021)
The relationship between China and Taiwan is on enduring rivalry for the last five decades regarding their identity, territory, and national sovereignty. From China's perspective, Taiwan is an inseparable part of Mainland China, therefore every forms of self independence are not accepted. Meanwhile from Taiwan's perspective, it is a sovereign state that doesn't abide to "One China, Two System” principle. The competition of those two often involves diplomacy to obtain formal recognition from other countries to maintain its legitimacy and rights as a state. On September 2019, Solomon Island, which had been in relationship for 36 years with Taiwan, decided to change its formal recognition and supported China. The author uses Joseph Nye Jr's Soft Power Theory with library research data collection methods and congruent data analysis methods. This paper aims to analyze the form of Taiwan and China policies through the concept of soft power and understanding the influence of those two countries' policies to the decision of the Solomon Island. The results proves that China's soft power is superior to Taiwan's soft power from the perspective of Solomon Islands.